Intravitreal Dexamethasone Implant for Acute Exudative Polymorphous Vitelliform Maculopathy. Issue 5 (September 2014) - Scupola, Andrea; Abed, Edoardo; Sammarco, Maria Grazia; Traina, Salvatore; Villano, Antonio; Grimaldi, Gabriela; Blasi, Maria Antonietta
Purpose: Acute exudative polymorphous vitelliform maculopathy is a rare retinal disease characterized by bilateral serous macular detachment and subretinal accumulation of yellowish deposits resembling Best dystrophy lesions. Corticosteroid systemic therapy has been used empirically in the attempt to treat this retinal disorder with mixed results. Thus, the benefit of corticosteroid remains undetermined. To our knowledge, we report the first case of acute exudative polymorphous vitelliform maculopathy (AEPVM) treated in one eye with intravitreal dexamethasone implant (Ozurdex; Allergan, Inc., Irvine, California, USA). Methods: A 28-year-old man with AEPVM underwent intravitreal dexamethasone implantation in the left eye. Results: Compared with the fellow eye, intravitreal dexamethasone implant did not significantly modify the clinical course of the disease. No implant-related complication was experienced during follow-up. Conclusions: The lack of response to intravitreal dexamethasone seems to suggest that corticosteroids may be ineffective for the treatment of AEPVM.